Effect of conventional EDM parameters on micromachined surface roughness and fabrication of hot embossing master and microtool - Ali, Mohammad Yeakub; S.M., Ammar (Taylor & Francis, 2009)
This article discusses the effect of conventional electrical discharge machining (EDM) parameters for generating micrometer and submicrometer leveled surface roughness. Fabrication of submillimeter-sized microstructure to use as a master microtool for replication of polymer microcomponents is also presented. Beryllium copper mold alloy was machined using very low values of three input parameters: discharge current, pulse-on time, and pulse-off time. The input parameters and measured surface roughness were analyzed, and statistical models were developed. The analysis showed that surface roughness increased with the increase of discharge current and pulse-on time. These models were applied to lower values of input parameters to achieve high surface finish. A hot embossing replication master with microchannel structure was produced using the optimized machining parameters with an average surface roughness of 0.60m. The replication master was tested with a prototype micro hot embossing machine where it faithfully duplicated its microstructures.